2018
DOI: 10.3389/fchem.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Modified ZnO Nanoparticles as Gas Sensors Array for Volatile Organic Compounds (VOCs)

Abstract: In this work a peptide based gas sensor array based of ZnO nanoparticles (ZnONPs) has been realized. Four different pentapeptides molecularly modeled for alcohols and esters having cysteine as a common spacer have been immobilized onto ZnONPs. ZnONPs have been morphologically and spectroscopically characterized. Modified nanoparticles have been then deposited onto quartz crystal microbalances (QCMs) and used as gas sensors with nitrogen as carrier gas. Analysis of the pure compounds modeled demonstrated a nice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…In some recent studies, molecular modeling has been successfully used to rationally design synthetic receptors for a variety of analytical applications, both in liquid [6][7][8][9] and in gas [10]. In our previous work, we have demonstrated that peptides selected by virtual screening are very efficient materials for sensing VOCs in food samples such as olive oil [11], chocolate [12], candies [13], fruit juices [14] and carrots [15].…”
Section: Introductionmentioning
confidence: 99%
“…In some recent studies, molecular modeling has been successfully used to rationally design synthetic receptors for a variety of analytical applications, both in liquid [6][7][8][9] and in gas [10]. In our previous work, we have demonstrated that peptides selected by virtual screening are very efficient materials for sensing VOCs in food samples such as olive oil [11], chocolate [12], candies [13], fruit juices [14] and carrots [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in artificial sensors, a nano-structuration of the sensing surface leads to an increase in the sensitivity. As a first example, the team of Dr. D. Compagnone [66,102,103] deposited functionalized nanoparticles on their sensors to increase the specific surface, as shown in Figure 7b. Zine et al [104] generated them directly in situ.…”
Section: Increase Of the Sensitivitymentioning
confidence: 99%
“…(a) Olfactory neurons deploy a large specific surface area in the mucus through their cilia. To mimic this strategy, (b) Mascini et al[103] modified ZnO nanoparticles with peptides, (c) Tanaka et al[82] immobilized peptides specific to benzaldehyde on ZnO nanowires. (d) Jaffar-Bandjee et al[108] fabricated artificial "moth antennae" (e) Gray et al[109] proposed liposomes displaying tetrameric peptides to enable cooperative binding (f) Kotlowski et al[96] used a bio-functional linker to optimize the orientation of OBPs on a graphitic surface.…”
mentioning
confidence: 99%
“…Using ZnO nanoparticles instead of AuNPs led to similar results regarding the discrimination ability between five alcohols and three esters. Furthermore, good results were obtained for distinguishing between the aroma profiles of water and fruit juices, where the latter is influenced by fruit and sugar content [147]. Both an array with eight metalloporphyrin-coated QCM sensors and an array with eight AuNP-peptide-coated QCM sensors were able to discriminate standard chocolate samples from artificially degraded chocolate samples with good accuracy, albeit the peptide-coated sensors showed a better prediction performance [148].…”
Section: Qcm Multi-sensor Arraysmentioning
confidence: 99%